Tumor budding in tumor tissue among operatively treated patients with lung adenocarcinoma - Vasilijević, Milena; Lovrenski, Aleksandra; Panjković, Milana (Vojnosanitetski pregled, 2021)
Background/Aim. The histological phenomenon of tumor budding is being recognized as an important determinant of disease progression and poor prognosis in various types of carcinoma. We aimed to evaluate the clinicopathological significance of tumor budding in adenocarcinoma of the lung. Methods. The study included 114 patients operatively treated for lung adenocarcinoma in a one-year period. Microscopic analysis of routine histological slides was performed to establish the presence and density of tumor buds. These results were compared in relation to gender, age, tumor size, nodal status, and pathological stage. Results. The budding-positive group included 34 (53.1%) men and 27 (54%) women. There were 30 (46.9%) men and 23 (46%) women in the budding-negative group. No statistical significant difference in age was found between males (64.3 ± 6.59 years) and females (63.1 ± 6.53 years) in the budding-positive group, nor in the budding-negative group (males 63.3 ± 6.02 years; females 63.2 ± 6.72 years). Statistically significant result in tumor size was found in females with the presence of tumor budding (p < 0.05). The budding-positive group of patients in nodal stage N1 and stage III of the disease pointed to the statistical significance (p < 0.05). Conclusion. With the statistical significance confirmed between the higher nodal status, higher pathological stage, and tumor budding found in this study, this histological phenomenon is still relatively new for the diagnostics domain of pathology. However, it increasingly receives attention as an adverse prognostic factor. These results may help tumor budding incorporate into the existing staging systems in addition to other factors known to be predictors of worse outcome.
Keywords: lung neoplasms; adenocarcinoma; neoplasm invasiveness; neoplasm staging; postoperative period; neoplasm recurrence, local